2022
DOI: 10.1155/2022/8385456
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin/BMP-2-Loaded Mesoporous Silica Nanoparticles for the Repair of Open Fractures with Bone Defects

Abstract: The study aimed to explore the feasibility of a nanodrug delivery system to treat open fractures with bone defects. We developed a cefazolin (Cef)/bone morphogenetic protein 2 (BMP-2)@mesoporous silica nanoparticle (MSN) delivery system; meanwhile, Cef/MBP-2@ poly(lactic-co-glycolic acid) (PLGA) was also developed as control. For the purpose of determining the osteogenic and anti-inflammatory actions of the nanodelivery system, we cultured bone marrow mesenchymal stem cells (BMSCs) and constructed a bone defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Based on the above advantages, MSN are often functionalized to form a multifunctional drug delivery system. Shen et al 69 developed an MSN-based dual drug delivery system that can simultaneously deliver cefazolin (Cef) and bone morphogenic protein-2 (BMP-2). Compared with a Poly-(D,L-lactide-co-glycolide) (PLGA) delivery system, the MSN group showed better permeability to the bone tissue and higher levels of bone marrow-derived MSC (BMSC) proliferation and migration ability, which is beneficial for accelerating bone repair.…”
Section: Np Carriers For Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above advantages, MSN are often functionalized to form a multifunctional drug delivery system. Shen et al 69 developed an MSN-based dual drug delivery system that can simultaneously deliver cefazolin (Cef) and bone morphogenic protein-2 (BMP-2). Compared with a Poly-(D,L-lactide-co-glycolide) (PLGA) delivery system, the MSN group showed better permeability to the bone tissue and higher levels of bone marrow-derived MSC (BMSC) proliferation and migration ability, which is beneficial for accelerating bone repair.…”
Section: Np Carriers For Bone Regenerationmentioning
confidence: 99%
“…Significant differences between groups are indicated as * P < 0.05, ** P < 0.01, *** P < 0.001. Reproduced with permission from ref . Copyright 2022 Hindawi.…”
Section: Np Carriers For Bone Regenerationmentioning
confidence: 99%
“…Yi et al 72 found that mesoporous silica nanoparticles-chitosan-loaded BMP-2 could effectively promote the repair of bone defects in chronic osteomyelitis and promote the osteogenic differentiation of BMSCs. Shen et al 73 found that Cefazolin/BMP-2 loaded mesoporous silica nanoparticles significantly promoted the repair of open fractures and reduced inflammation with bone defects in mice, and increased the osteogenic differentiation ability of BMSCs in vitro . Qiu et al 74 prepared silk fibroin/chitosan scaffolds containing mesoporous hydroxyapatite nanoparticles (mHANPs) of BMP-2 (SCH-L).…”
Section: Applications Of Nanoparticles In Bone Regenerationmentioning
confidence: 99%
“…Dentin matrix extract protein (DMEP) was identified as a complex GF mixture, and MSNs loaded with DMEP were demonstrated to promote cartilage regeneration in vitro and in vivo [ 97 ]. To mitigate the risk of infection in defective bone tissue, a study showed that co-loading the antibiotic cefazolin with BMP-2 into MSNs significantly increased new bone formation and reduced the release of inflammatory factors IL-1 and IL-4 in a mouse fracture model [ 98 ]. The flexible surface of MSNs also provides alternative loading methods for growth factors.…”
Section: Exogenous Growth Factor Deliverymentioning
confidence: 99%